CO 2 upgrading into bioproducts using a two-step abiotic–biotic system - Geonhui Lee; Hye-Jin Jo; Jihoon Choi; Maria Fonseca Guzman; Yu Shan; Han K. D. Le; Julian Feijoo; Nathan Soland; Douglas S. Clark; Peidong Yang (Proceedings of the National Academy of Sciences, 2025)
The valorization of CO 2 to chemicals beyond C 1-2 products is receiving significant interest; however, the direct electrosynthesis of C n molecules (n > 4) remains a challenge. Here, we present a two-step abiotic–biotic system for upgrading CO 2 into the biopolymer, poly(3-hydroxybutyrate). In the electrolysis system, CO 2 is converted into C 2 oxygenates using a Cu–Ag tandem electrocatalyst. The electrolysis process generates a liquid stream containing ~ 200 mM acetate in a bio-compatible electrolyte. This electrosynthesized acetate is then fed to a bioreactor, where the substrate is upgraded by Cupriavidus necator to biopolymer with a maximum rate of 32 ± 3.5 mg L −1 h −1 . We further demonstrate the purification of the resulting biopolymer into a powder. The high productivity of the abiotic–biotic system demonstrates its feasibility for sustainable chemical manufacturing.